Mechanism evaluation of a lifestyle intervention for patients with musculoskeletal pain who are overweight or obese: protocol for a causal mediation analysis. Issue 6 (3rd July 2017) - Lee, Hopin; Wiggers, John; Kamper, Steven J; Williams, Amanda; O'Brien, Kate M; Hodder, Rebecca K; Wolfenden, Luke; Yoong, Sze Lin; Campbell, Elizabeth; Haskins, Robin; Robson, Emma K; McAuley, James H; et al.
Abstract : Introduction: Low back pain (LBP) and knee osteoarthritis (OA) are highly prevalent and disabling conditions that cause societal and economic impact worldwide. Two randomised controlled trials (RCTs) will evaluate the effectiveness of a multicomponent lifestyle intervention for patients with LBP and knee OA who are overweight or obese. The key targets of this intervention are to improve physical activity, modify diet and correct pain beliefs. These factors may explain how a lifestyle intervention exerts its effects on key patient-relevant outcomes: pain, disability and quality of life. The aim of this protocol is to describe a planned analysis of a mechanism evaluation for a lifestyle intervention for overweight or obese patients with LBP and knee OA. Methods and analysis: Causal mediation analyses of 2 two-armed RCTs. Both trials are part of a cohort-multiple RCT, embedded in routine health service delivery. In each respective trial, 160 patients with LBP and 120 patients with knee OA waiting for orthopaedic consultation will be randomised to a lifestyle intervention, or to remain part of the original cohort. The intervention consists of education and advice about the benefits of weight loss and physical activity, and the Australian New South Wales Get Healthy Service. All outcome measures including patient characteristics, primary and alternative mediators, outcomes, and potential confounders will be measured at baseline (T0). The primary mediator, weight, will be measured at 6 months post randomisation; alternative mediators including diet, physical activity and pain beliefs will be measured at 6 weeks post randomisation. All outcomes (pain, disability and quality of life) will be measured at 6 months post randomisation. Data will be analysed using causal mediation analysis with sensitivity analyses for sequential ignorability. All mediation models were specified a priori before completing data collection and without prior knowledge about the effectiveness of the intervention. Ethics and dissemination: The study is approved by the Hunter New England Health Human Research Ethics Committee (13/12/11/5.18) and the University of Newcastle Human Research Ethics Committee (H-2015–0043). The results will be disseminated in peer-reviewed journals and at scientific conferences. Trial registration number: ACTRN12615000490572 and ACTRN12615000478516; Pre-results.